From Music Performance to Prescription: A Guide for Musicians and Health Professionals - Melissa Forbes; Genevieve A. Dingle; Nick Aitcheson; Christa Powell (Music & Science)
Through social prescribing, healthcare systems can systematically support musical care by connecting individuals with community music programs and skilled practitioners. Social prescribing is a non-medical approach to health in which individuals with unmet social needs are referred to community programs like choir singing and music-making. This article addresses the challenges of integrating music programs into healthcare—music on prescription—despite growing interest in the benefits. For instance, musicians may be enthusiastic but lack preparation for working in health and social care settings. On the other hand, healthcare professionals may either be unfamiliar with the benefits of music prescription or uncertain about implementing referral pathways. The historical divide between the arts and health sectors further complicates the implementation of music prescription programs. Drawing on our expertise in arts in health, music performance and education, community music, clinical psychology, and medicine, the article highlights how musicians’ skills and professional identities evolve across performance, education, and health domains. We also offer advice for health professionals on developing referral pathways to music prescription programs. The article emphasizes the importance of music education in preparing musicians and concludes by encouraging collaboration between musicians and healthcare providers to develop sustainable music prescription programs. By establishing structured referral pathways, social prescribing offers a systematic framework for delivering musical care within healthcare settings, while ensuring that music interventions remain focused on addressing participants’ social and health needs.